HuR interacts with lincBRN1a and lincBRN1b during neuronal stem cells differentiation. Issue 10 (3rd October 2019) - Carelli, Stephana; Giallongo, Toniella; Rey, Federica; Latorre, Elisa; Bordoni, Matteo; Mazzucchelli, Serena; Gorio, Maria Carlotta; Pansarasa, Orietta; Provenzani, Alessandro; Cereda, Cristina; Di Giulio, Anna Maria
ABSTRACT: LncRNAs play crucial roles in cellular processes and their regulatory effects in the adult brain and neural stem cells (NSCs) remain to be entirely characterized. We report that 10 lncRNAs (LincENC1, FABL, lincp21, HAUNT, PERIL, lincBRN1a, lincBRN1b, HOTTIP, TUG1 and FENDRR) are expressed during murine NSCs differentiation and interact with the RNA-binding protein ELAVL1/HuR. Furthermore, we characterize the function of two of the deregulated lncRNAs, lincBRN1a and lincBRN1b, during NSCs' differentiation. Their inhibition leads to the induction of differentiation, with a concomitant decrease in stemness and an increase in neuronal markers, indicating that they exert key functions in neuronal cells differentiation. Furthermore, we describe here that HuR regulates their half-life, suggesting their synergic role in the differentiation process. We also identify six human homologs (PANTR1, TUG1, HOTTIP, TP53COR, ELDRR and FENDRR) of the mentioned 10 lncRNAs and we report their deregulation during human iPSCs differentiation into neurons. In conclusion, our results strongly indicate a key synergic role for lncRNAs and HuR in neuronal stem cells fate.